A quem pertence o corpo do homem preto e gay?: Racismo afetivo-sexual e os efeitos deletérios na saúde mental dos homens pretos e gays - Rodrigues, Hênio dos Santos (2025)
Affective-sexual racism* is configured as a process of neglect, objectification, hypersexualization, and silencing of Black people in affective and sexual dynamics, hindering the full experience of positive affective and sexual relationships due to skin color. Thus, the affective and sexual environment for non-White people in Brazil is permeated by less tangible dynamics, as the racial issues (e.g., violence, exclusion, discrimination) that interfere with the daily and public lives of Black people also impact the most intimate and private spheres (e.g., relationships and affective and sexual life) since ancient times. Such experiences take on doubly significant contours and impacts when race and sexual identity intersect, that is, when we aim to evaluate the impacts of affective-sexual racism on the mental health of Black gay men in Brazil. Given these premises, the present research project was developed with the general objective of investigating the experience of affective-sexual racism by Black gay men and, concomitantly, evaluating the impacts of this type of racism on their mental health. Specifically, it aims to: a) identify the main aspects of affective-sexual racism in the literature; b) transpose international findings on affective-sexual racism to possible applicability in the Brazilian reality; c) develop a measure to enable the assessment of affective-sexual racism, considering the plurality of the Brazilian context; d) develop a comparative study between Black, mixed-race, and White men, aiming to validate the existence and impacts of affective-sexual racism in Black gay men compared to the other two racial groups. To achieve the proposed objectives, four studies will be conducted and presented in the chapters of this work. Chapter 1 presents a theoretical study on the phenomenon of affective-sexual racism and its nuances when analyzed in the context of the experiences of Black gay men, highlighting the subtleties that shape this dynamic. Chapter 2 will conduct a scoping review of recent scientific literature, aiming to analyze data related to the process of exclusion through affective-sexual racism and its impacts on the mental health of non-White gay men. Chapter 3 presents a psychometric study for the construction and validation of the Affective-Sexual Racism Experience Scale (EVRAS) in a population of selfidentified Black individuals. The results showed that Black individuals experience affectivesexual racism via a three-factor scale (neglect, objectification, and silencing). Data from this study confirm the existence of affective-sexual racism and illustrate how the phenomenon limits the affective-sexual trajectory of Black individuals in Brazil. Chapter 4 consists of a quantitative study aimed at comparing the experience of affective-sexual racism among nonWhite (Black and mixed-race) and White gay men, with the goal of improving EVRAS indices and determining whether the phenomenon exists in this context, as well as whether it reveals deleterious effects on participants’ mental health. The results derived from the EVRAS analyses show that affective-sexual racism is experienced to a greater extent by Black and mixed-race gay men, and that, to some degree, their mental health is compromised. Thus, it is expected that the results of these studies will provide answers about affectivesexual racism, as well as stimulate research into the impacts of this facet of racism on the mental health of Black people in Brazil.